The Effect of Debt to Equity Ratio, Earning Per Share and Company Size on Market Value of Equity With Intellectual Capital As Moderating Variable - Senja Milanda; Edyanus Halim; Enni Savitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The purpose of this study was to examine the effect of debt-to-equity ratio, earnings per share, and company size on market value of equity. In this study, intellectual capital was used as a moderating variable. The samples in this study are companies listed in manufacturing companies in 2017-2019 periods on the IDX. Data was processed using the method of moderated regression analysis (Rev Mou1). The results of this study found that debt to debt-to-equity ratio and company size affect the market value of equity meanwhile earning per share can’t affect the market value of equity. Intellectual capital can moderate the effect of debt-to-equity ratio and company size on market value of equity. Based on the results, intellectual capital cannot moderate the effect of earnings per share on market value of equity.